Scale design for evaluating the methodological quality of studies related to nutritional values of silages for ruminants. Pilot study - Torres, Mildrey; Rodríguez, R.; Herrera, Magaly (Cuban Journal of Agricultural Science, 2018)
In order to propose a specific scale that allows to evaluate the methodological quality of studies related to chemical composition and nutritional value of silages to be included in meta-analysis, the criteria of PEDro scale were used, referring to sample taking, the randomization of treatments to experimental units and informed statistical information. In addition, other criteria were included, such as the characteristics of forage for silage, description of silage preparation process, used chemical analysis procedures, statistical methods used in the experimentation and the information or not about key variables of chemical and fermentative composition. To identify the criteria that made up the scale, 80 articles were analyzed and, for its validation, 40 articles of the theme were used. For the search and selection of articles, EBSCO, Scielo, Science Direct and Researchgate databases were used, and, to validate the scale, reliability between two evaluators was determined by the intraclass correlation coefficient. The scale proposal assessed 12 criteria and considers that a study is accepted, as of good methodological quality, if it meets 9 or more criteria. Validation between two evaluators, independently, resulted in excellent reliability, with an intraclass correlation coefficient of 0.81 (I.C95 % 0.67-0.89). The new scale thus becomes an appropriate tool, which will minimize biases and improve quality of the selected studies to develop the meta-analysis on this subject. Keywords: silage, meta-analysis, evaluation criteria, reliability